Leveraging liquid biopsy to uncover resistance mechanisms and guide personalized immunotherapy - Zeinab Dalloul; Jana Grenel Briend; Mariama Diawara; Catherine Taylor; Rodney J. Ouellette (Translational Oncology)
Cancer therapy has been revolutionized by immune checkpoint inhibitors (ICIs) that create a new paradigm among cancer immunotherapies. These agents restore the immune system capacity to fight cancer through blocking the action of major immune checkpoint proteins that suppress immune responses such as programmed cell death protein 1 (PD-1), programmed death-ligand 1 (PD-L1) and cytotoxic T-lymphocyte-associated protein 4 (CTLA-4), which tumors exploit for immune escape. Another advancement is the absence of known biomarkers involves ICIs, which can further be translated into new liquid tests like liquid biopsies, indicating the immune status of the patient. Liquid biopsy is a minimally invasive method for identifying tumor-derived components such as circulating tumor cells, cell-free DNA and extracellular vesicles (EVs) from body fluids for analysis. Researchers increasingly use liquid biopsy for biomarkers discovery and patient stratification into clinical applications. Even though immunotherapy has great advances, still there are obstacles faced while using ICIs. Many patients fail to respond to the treatment because of the heterogeneous mechanisms of resistance. Immunotherapy resistance is a dynamic interplay between tumors and their surrounding stroma. To understand this variability, humanized mice models are increasingly used for mirroring human immune responses. Such models offer insight into cancer immunotherapy when human immune system is engrafted into mice, and EV and biomarker profiles are established in those models. EVs reflect differences in tumor characteristics and the immune landscape around tumors to develop personalized strategies to enhance ICI efficacy. This may improve patient prognosis, giving reason to hope for better, more effective treatments.